2021
DOI: 10.1530/ec-21-0267
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of the calcium/phosphate ratio for primary hyperparathyroidism in southwest China

Abstract: Background: The diagnosis of primary hyperparathyroidism (PHPT) remains a challenge because of increased asymptomatic PHPT or patients with normocalcaemic PHPT (NPHPT). In addition, some primary hospitals in China have no equipment to measure PTH levels. Therefore, an additional, simple, and inexpensive laboratory biochemical marker is urgently needed. The calcium/phosphate (Ca/P) ratio and chloride/phosphate (Cl/P) ratio have been proposed as suitable tools to diagnose PHPT in Europe; however, the Ca/P ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When this ratio was evaluated in 35 patients with NPHPT, the sensitivity decreased to 71%, while the specificity of 88% was maintained. A recent study in the Chinese population confirmed that a Ca/P ratio of over 2.94 can distinguish PHPT patients from healthy controls with a sensitivity of 95.5% and a specificity of 98.7% 11 . In this study, we aimed to investigate the diagnostic value of serum Ca/P ratio in PHPT screening in our patient population with PHPT.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…When this ratio was evaluated in 35 patients with NPHPT, the sensitivity decreased to 71%, while the specificity of 88% was maintained. A recent study in the Chinese population confirmed that a Ca/P ratio of over 2.94 can distinguish PHPT patients from healthy controls with a sensitivity of 95.5% and a specificity of 98.7% 11 . In this study, we aimed to investigate the diagnostic value of serum Ca/P ratio in PHPT screening in our patient population with PHPT.…”
Section: Introductionmentioning
confidence: 93%
“…In another study by Madeo et al 15 involving 142 patients diagnosed with NPHPT, the Ca/P ratio cutoff value of 2.55 showed high sensitivity (71.1%) and specificity (87.9%). Yin et al 11 recently reported a sensitivity of 95.5% and specificity of 98.7% with a Ca/P ratio cutoff value of 2.94, and this index was positively correlated with the PTH level (r=0.875, p<0.001). In another study, the cutoff value of 2.55 for the Ca/P ratio served as a reliable predictor for the diagnosis of PHPT with 95.6% sensitivity and 63.6% specificity 16 .…”
mentioning
confidence: 95%
“…The serum calcium (Ca)–to–phosphorous (P) (Ca/P) ratio has been proposed as a simple tool to detect disorders of Ca and P metabolism such as primary hyperparathyroidism (PHPT) and chronic hypoparathyroidism (HPT) ( 1 4 ). In detail, it has been demonstrated that the serum Ca/P ratio is highly accurate in detecting PHPT when above 2.55 (3.3 if serum Ca and P are expressed in mg/dL) and HPT when below 1.78 (2.32 if serum Ca and P are expressed in mg/dL) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%